2005
DOI: 10.1002/cpp.436
|View full text |Cite
|
Sign up to set email alerts
|

Therapy via videoconferencing: a route to client empowerment?

Abstract: This study examines the clinical utility of cognitive behavioural therapy delivered via videoconferencing for bulimic disorders, and factors associated with adjustment to this mode of treatment delivery. A single-case-series design was used with six participants with bulimic disorders. Most were living in remote areas in north-east Scotland or Shetland. Therapy sessions were conducted weekly at a bandwidth of ISDN 6 (384 kbytes/sec) via videoconferencing links between local community hospital sites and the eat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
107
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(125 citation statements)
references
References 18 publications
15
107
0
3
Order By: Relevance
“…Several studies reported on outpatient services that were developed in collaboration with larger hospitals, such as services for people with eating disorders, which used videoconferencing to connect participants in community hospital sites and a specialist service within a large urban hospital for weekly therapy sessions. 65 Another example was the development of a teleopthalmology service by a regional hospital in Western Australia together with eye specialists in Perth, which allowed digital images to be transmitted to the specialists for diagnosis. 44 Two studies described outreach chemotherapy services, delivering chemotherapy cycles in community hospitals by staff based at a larger hospital or care centre.…”
Section: Community Hospitals In Selected High-income Countries: a Scomentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies reported on outpatient services that were developed in collaboration with larger hospitals, such as services for people with eating disorders, which used videoconferencing to connect participants in community hospital sites and a specialist service within a large urban hospital for weekly therapy sessions. 65 Another example was the development of a teleopthalmology service by a regional hospital in Western Australia together with eye specialists in Perth, which allowed digital images to be transmitted to the specialists for diagnosis. 44 Two studies described outreach chemotherapy services, delivering chemotherapy cycles in community hospitals by staff based at a larger hospital or care centre.…”
Section: Community Hospitals In Selected High-income Countries: a Scomentioning
confidence: 99%
“…Use of telemedicine often involved direct interaction between the specialist and the patient, such as a teleophthalmology service in Australia. 44 Other examples include the provision of a medical oncology outreach clinic, whereby oncologists from a larger hospital review patients in the community hospital using video conferencing equipment, 69 therapy sessions delivered by videoconference, 65 videoconference fracture clinics, 50 telepharmacy 86 and remote commenting by radiographers. 87 In the Grampian region of Scotland, a minor injuries telemedicine network connects 15 minor injury units in community hospitals to the emergency department at the regional teaching hospital.…”
Section: Community Hospitals In Selected High-income Countries: a Scomentioning
confidence: 99%
“…(Mitchell, Meyers, Swan-Kremeier, & Wonderlich, 2003). Por sua vez, pacientes relataram que, ao se ajustar ao vĂ­deo, a relação com o terapeuta diferiu das relaçÔes face a face, mas nĂŁo necessariamente de modo pior ou melhor (Simpson, Bell, Knox, & Mitchell, 2005). Em outro estudo (Himle et al, 2006) …”
unclassified
“…UK and US studies report good patient satisfaction (Cruz 2005;Norman 2006), with patients reporting a sense of security and of greater control of the situation, feeling less threatened and less inhibited (Simpson 2005). Clinicians report slightly lower levels of satisfaction than patients in some studies, which may reflect clinician anxiety about picking up non-verbal communication such as eye contact, facial expressions and subtle changes in voice quality, which may be important in determining the patient's emotional state.…”
Section: Literature Reviewmentioning
confidence: 96%